Nas páginas do livro-mundo, travessias do alfabetizar: saberes e práticas de professores alfabetizadores do TOPA/UEFS - Barros, Ludimila de Oliveira (2016)
This paper seeks to understand the pedagogical practices of literacy teachers from the Todos pela Alfabetização Program implemented by Universidade Estadual of Feira de Santana (TOPA / UEFS) and the knowledge mobilized by them in their literacy "crossings". The investigation lies in the field of qualitative research, based on the emerging paradigm of science (SANTOS, 1995), in connection with the approach of the History of Everyday Life (CERTEAU, 1998). The locus of this study was the city of Feira de Santana, where literacy teachers from TOPA have served as collaborators. There were a total of six respondents in this research: five literacy teachers from TOPA and a general coordinator of the program during the years of 2007-2011. In addition to the narrative interviews, UEFS‟s Pró Reitoria de Extensão (PROEX/UEFS) provided documents used for training teachers from TOPA that were employed in the production of data analysis contained in this work. Academic reflections were woven from the theoretical and methodological assumptions of the Youth and Adult Education (Freire, 2011), in connection with the field of Teacher Training and Teacher Knowledges (Tardif, 2012; CHARLOT, 2000). Of the many lessons learned, it is clear that learning and teaching to read necessarily entails the understanding of the world around us and the seizure of the realities that reach us. This interpretation has helped us to think about the everyday life and the experiences in the routine processes of life-training, as producers of experiential knowledge that are so important to the teaching practice. Thus, it can be concluded that: 1) the pedagogical practice of literacy teachers from TOPA / UEFS are necessarily involved with their own cultural repertoires and with their learners‟; 2) the literacy teachers from TOPA / UEFS in their everyday classrooms, give other meanings to the teaching training they receive in order to obtain success in literacy processes; and 3) the knowledge mobilized by literacy teachers in their literacy crossings intermingle with their experiences of "existing and being" on / with the world.